Effects of electromyostimulation on performance parameters in sportive and trained athletes: A systematic review and network meta-analysis - Micke, F.; Held, S.; Lindenthal, J.; Donath, L. (European Journal of Sport Science, 2022)
This systematic review and network meta-analysis aimed to evaluate the effectiveness of different electromyostimulation (EMS) interventions on performance parameters in athletes. The research was conducted until May 2021 using the online databases PubMed, Web of Science, Cochrane and SPORTDiscus for studies with the following inclusion criteria: (a) controlled trials, (b) EMS trials with at least one exercise and/or control group, (c) strength and/or jump and/or sprint and/or aerobic capacity parameter as outcome (d) sportive/trained subjects. Standardized mean differences (SMD) with 95% confidence interval (CI) and random effects models were calculated. Thirty-six studies with 1.092 participants were selected and 4 different networks (strength, jump, sprint, aerobic capacity) were built. A ranking of different exercise methods was achieved. The highest effects for pairwise comparisons against the reference control "active control" were found for a combination of resistance training with superimposed EMS and additional jump training (outcome strength: 4.43 SMD [2.15; 6.70 CI]; outcome jump: 3.14 SMD [1.80; 4.49 CI]), jump training with superimposed whole-body electromyostimulation (WB-EMS) (outcome sprint: 1.65 SMD [0.67; 2.63 CI]) and high intensity bodyweight resistance training with superimposed WB-EMS (outcome aerobic capacity: 0.83 SMD [-0.49; 2.16 CI]). These findings indicate that the choice of EMS-specific factors such as the application mode, the combination with voluntary activation, and the selection of stimulation protocols has an impact on the magnitude of the effects and should therefore be carefully considered, especially in athletes. Superimposed EMS with relatively low volume, high intensity and outcome-specific movement patterns appeared to positively influence adaptations in athletes.